2013
DOI: 10.1002/qua.24537
|View full text |Cite
|
Sign up to set email alerts
|

Geometries, vibrational frequencies, and excitation energies of a series of fluorine-substituted carbenes, FCX (X = H, F, Cl, Br, and I): A high-level multireference configuration interaction study

Abstract: High-level calculations using internally contracted multireference configuration interaction including Davidson correction (icMRCI1Q) method have been carried out for the ground singlet states, the first excited states, and the lowest triplet states of a series of fluorine-substituted carbenes FCX (X 5 H, F, Cl, Br, and I). Equilibrium geometries and vibrational frequencies of the three electronic states, adiabatic transition energy of the first excited singlet state, as well as the ground singletlowest triple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 71 publications
2
13
2
Order By: Relevance
“…Such conclusion was deduced with the aid of comparing the calculated result of CFBr at the same theoretical levels with the experimental barrier reported by Knepp et al 24 Since no experimental results of the Ã1A″ state of CFI is available to compare with the calculation results, further study of the PES at higher levels of theory should be carried out. In fact, in the case of CFBr, Knepp's experimental results 24 were debated by Truscott et al 17 in their recent high-resolution LIF spectroscopic study, which reassigned the T 00 value of the Ã1A″ state to 23271 cm −1 (2365 cm −1 higher than Knepp's result 24 and is consistent with several following theoretical studies 18,20,22 ) and estimated the barrier height about 1000 cm −1 from fluorescence quantum yields (in contrast to Knepp's result of 3360 cm −124 ). In addition, a recent study 22 has demonstrated that the scalar relativistic effect, spin−orbit coupling (SOC), and core− valence (CV) effect should be considered in the calculation to obtain reliable energies of CFBr, which has not been investigated in CFI carbene.…”
Section: ■ Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…Such conclusion was deduced with the aid of comparing the calculated result of CFBr at the same theoretical levels with the experimental barrier reported by Knepp et al 24 Since no experimental results of the Ã1A″ state of CFI is available to compare with the calculation results, further study of the PES at higher levels of theory should be carried out. In fact, in the case of CFBr, Knepp's experimental results 24 were debated by Truscott et al 17 in their recent high-resolution LIF spectroscopic study, which reassigned the T 00 value of the Ã1A″ state to 23271 cm −1 (2365 cm −1 higher than Knepp's result 24 and is consistent with several following theoretical studies 18,20,22 ) and estimated the barrier height about 1000 cm −1 from fluorescence quantum yields (in contrast to Knepp's result of 3360 cm −124 ). In addition, a recent study 22 has demonstrated that the scalar relativistic effect, spin−orbit coupling (SOC), and core− valence (CV) effect should be considered in the calculation to obtain reliable energies of CFBr, which has not been investigated in CFI carbene.…”
Section: ■ Introductionsupporting
confidence: 71%
“…The Ã1A″ state of CFI, along with other fluorine-containing carbenes, was investigated very recently by Sun et al using a high-level icMRCI+Q/ccpV5Z theory. 20 In their study, by taking CFBr as an example, Sun et al also indicated that large basis sets and highly correlated methods are necessary to achieve reliable results for high-Z fluorine-containing carbenes.…”
Section: ■ Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The computed geometries and frequencies of theX,ã andà states are consistent with the theoretical literature values [23,[29][30][31]65,[68][69][70].…”
Section: Thex( 1 a )ã( 3 A ) Andã( 1 A ) States Of Cbri CCLI And Cfisupporting
confidence: 86%
“…Consequently, the singlet-triplet separations computed in this work are not too different from those obtained at lower levels of theory [23,31,64,69]. Surprisingly though, in the case of CFI there is a noticeable discrepancy between the current result of 27.3 kcal mol −1 and the value of 25.1 kcal mol −1 (8777 cm −1 ) that has been recently reported by Sun et al [70] computed at a comparable level of theory with that employed here. The current result is, however, consistent with the CCSD(T) and MRCI + Dav results of Hajgató et al [23], that range from 27.1 to 28.6 kcal mol −1 .…”
Section: Singlet-triplet Splittingscontrasting
confidence: 76%